A New Era in Metastatic Prostate Cancer: The Combination of Chemotherapy and Hormonal Treatment as Initial Treatment - TİNAY, İLKER (GALENOS YAYINCILIK, 2016)
In recent years, studies have been reported about the combination of androgen deprivation therapy (ADT) and different chemotherapy modalities as the initial therapy in newly-diagnosed patients with hormone-sensitive metastatic prostate cancer and recently, possible effects of docataxel chemotherapy in combination with ADT was evaluated in the 2 multi-institutional randomized trials from North America (CHAARTED) and Europe (GETUG-AFU-15). We reviewed the data for the current use of chemo-hormonal therapy as the initial treatment modality in castration-sensitive metastatic prostate cancer. New findings of CHAARTED trial showed that combination of ADT with docetaxel chemotherapy conferred a significant median over-all survival benefit over ADT alone and patients with high-volume disease derived a 17-month gain in median over-all survival. However in GETUG trial, while no over-all survival benefit was observed between two groups however combination therapy was associated with an improvement in biochemical and clinical progression-free survivals. The combination of docetaxel-based chemotherapy with ADT as the initial treatment seems as a promising treatment alternative in patients with hormone-sensitive metastatic prostate cancer, especially in patients with high-volume disease.
Keywords: Metastatic prostate cancer; chemotherapy; hormonal treatment; combination; ANDROGEN-DEPRIVATION THERAPY; PREDNISONE; DOCETAXEL